Strengthening of Earthen Material with Some Binding Materials for Traditional and Contemporary Adobe Buildings - Gürdal, Erol; Karagüler, Mustafa Erkan (İstanbul Üniversitesi, 2023)
This study investigates the effects on adobe soils of adding varying amounts of gypsum, gypsum-lime, and lime to clay soils of different characteristics for replacing traditional adobe. This research focuses on stabilizing soil to enhance adobe’s structural integrity, making it a feasible option for modern constructions and renovations. The study investigates four types of clay soils with varying mineralogical compositions to produce adobe with different qualities. Results indicate that the introduction of gypsum contributes to reduced unit volume weight, increased void ratio, decreased thermal conductivity, and enhanced compressive strength. The research assesses the impact of water on adobe, including capillary rise and resistance to sprinkling. Moreover, the study explores the potential of gypsum-adobe to address the increasing demand for affordable and sustainable housing, especially in rural areas, contributing to energy conservation and cost-effectiveness. This study presents the advantages of utilizing adobe produced by this method in rural regions, in comparison to the building materials it may substitute.
Keywords: Architecture (Other); Mimarlık (Diğer)